1987
DOI: 10.1029/jb092ib13p13801
|View full text |Cite
|
Sign up to set email alerts
|

Shear instability in a viscoelastic material as the cause of deep focus earthquakes

Abstract: The mechanism of deep focus earthquakes has been examined by numerical and linear analysis of shear instability in subducting slabs. We assume subducting slabs deform such that the spatially averaged strain rate becomes time independent. Furthermore, we assume that rheology depends on temperature in the manner of an activation process. Using this model, we investigate quantitatively the conditions under which shear instability takes place, i.e., the deformation in the material concentrates in a thin layer wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
190
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(198 citation statements)
references
References 28 publications
6
190
0
2
Order By: Relevance
“…A number of processes have been suggested for causing local weakening. These include shear instabilities (Ogawa, 1987;Kelemen and Hirth, 2007), thermal runaways (John et al, 2010), and local weakening and embrittlement of the crust due to dehydration (e.g., Raleigh and Paterson, 1965;Kirby et al, 1996;Seno and Yamanaka, 1996;Hacker et al, 2003;Yamasaki and Seno, 2003). Possible consequences of dehydration include stress changes to the change in volume of the oceanic crust , pore pressure changes (Wong et al, 1997) or just the release and transport of water (e.g., Jung et al, 2004;John and Schenk, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A number of processes have been suggested for causing local weakening. These include shear instabilities (Ogawa, 1987;Kelemen and Hirth, 2007), thermal runaways (John et al, 2010), and local weakening and embrittlement of the crust due to dehydration (e.g., Raleigh and Paterson, 1965;Kirby et al, 1996;Seno and Yamanaka, 1996;Hacker et al, 2003;Yamasaki and Seno, 2003). Possible consequences of dehydration include stress changes to the change in volume of the oceanic crust , pore pressure changes (Wong et al, 1997) or just the release and transport of water (e.g., Jung et al, 2004;John and Schenk, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Several proposed mechanisms for deep earthquakes, including plastic shear instabilities [Ogawa, 1987] and frictional melting [Kanarnori et al, 1997], would be expected to show a strong temperature dependence. The form of this temperature dependence may provide one of the few observational constraints on the mechanism of deep earthquakes.…”
Section: Implications For the Mechanism Of Deep Earthquakesmentioning
confidence: 99%
“…In this paper we wish to address the role played in the plate-breaking problem by lithospheric elasticity coupled to a temperature-dependent visco-plastic rheology. Previous work based on a one-dimensional time-dependent model [Ogawa, 1987] has demonstrated that visco-elasticity could be a very efficient mechanism for transferring rather rapidly potential energy from elasticity into shear heating, which might cause deep-focus earthquakes. The conversion of elastic strain energy to shear heating can potentially be an attractive mechanism for facilitating localized deformation in the lithosphere.…”
Section: Introductionmentioning
confidence: 99%